2021
DOI: 10.3390/en14041081
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Machine Learning Models for Day-Ahead Photovoltaic Power Production Forecasting

Abstract: A main challenge for integrating the intermittent photovoltaic (PV) power generation remains the accuracy of day-ahead forecasts and the establishment of robust performing methods. The purpose of this work is to address these technological challenges by evaluating the day-ahead PV production forecasting performance of different machine learning models under different supervised learning regimes and minimal input features. Specifically, the day-ahead forecasting capability of Bayesian neural network (BNN), supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Finally, optimal prediction performance for each reference PV system predictive model was achieved by including the input features of the on‐site forecasted GHI, Tamb and solar angles of φs and α, against the output variable of the maximum power Pmp [56].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, optimal prediction performance for each reference PV system predictive model was achieved by including the input features of the on‐site forecasted GHI, Tamb and solar angles of φs and α, against the output variable of the maximum power Pmp [56].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work demonstrated that ML models constructed with input feature combinations from computed NWP models and solar position algorithms (forecasted irradiance, temperature, and the Sun's position angles) outperformed any other input parameter selection [56]. This is attributed to the correction of underlying biases of NWP forecasted data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar work that implements conventional ML algorithms for PV output power forecasting has also been pursued by others. SVM [62], BNN (Binarized Neural Network), SVR, and RT [63], and ANN [64], [65] are few examples. An important limitation of implementing the above methods arises when they are used for a PV plant located in a region where large and sudden weather variations over a short period are frequent.…”
Section: ) Ai-based Modelsmentioning
confidence: 99%